Completing Ostrom's table: A note on the taxonomy of goods - Emmanuel S. de Dios (University of the Philippines, School of Economics (UPSE), 2015)
A framework is proposed to subsume public goods and common-pool resources, respectively, as specific cases of positive and negative externalities. A pure public good is a positive externality whose appropriable benefits are too small or too uncertain relative to the high private cost for anyone to produce it in any amount. The common-pool problem is a case where each agent's action imposes a negative externality on everyone else.
Keywords: D61; D62; H41; H42; 330; public goods; common-pool resources; positive and negative externalities